The association between attributions of responsibility for motor vehicle accidents and patient satisfaction: a study within a no-fault injury compensation system. (May 2015) - Thompson, Jason; Berk, Michael; O'Donnell, Meaghan; Stafford, Lesley; Nordfjaern, Trond
Objective: This study set out to test the relationship between attributions of responsibility for motor vehicle accidents and satisfaction with personal injury compensation systems. Design: The study analysed survey data from 1394 people injured in a motor vehicle accident who were compensated under a no-fault personal injury compensation system. Patients' ratings of satisfaction with the compensation system across five domains (resolves your issues, keeps you up-to-date, treats you as an individual, cares about you, and overall satisfaction) were analysed alongside patient attributions of responsibility for their accident (not responsible, partly responsible, totally responsible). Postaccident physical and mental health status, age, gender, and duration of compensation claim were controlled for in the analysis. Results: A multivariate analysis of covariance indicated attributions of responsibility for accidents were significantly associated with levels of patient satisfaction across all five domains under study ( F (10, 2084) = 3.7, p < 0.001, η 2 = 0.02). Despite access to virtually indistinguishable services, patients who attributed responsibility for their accidents to others were significantly less satisfied with the injury compensation system than those who attributed responsibility to themselves. Conclusions: Satisfaction with no-fault motor vehicle injury compensation services are associated with patients' attributions of responsibility for their accident. Compensation systems and other rehabilitation services monitoring patient satisfaction should adjust for attributions of responsibility when assessing levels of patient satisfaction between time periods, services, or injured populations. Differences in levels of patient satisfaction observed between compensation or rehabilitation populations may reflect differences in attributions of responsibility for accidents rather than objective service quality.